Pengaruh Mentoring terhadap Kualitas Pemuda pada Organisasi Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) Medan - Zulhidayat, Zulhidayat; Rujiman, Rujiman; Rahmanta, Rahmanta (Mahesa Research Center, 2023)
The research was conducted at the Indonesian Muslim Student Action Organization (KAMMI) Medan from May to July 2017 on the Influence of Mentoring on Youth Quality at Indonesian Muslim Student Action Organization (KAMMI) Medan using questionnaire and observation method. From the research result obtained that Implementation of mentoring and execution of duty have positive effect to quality of life of youth. The success of a mentoring program depends on the participation and participation of youth in following mentoring. As for the respondents of this research is all KAMMI Medan officials who follow the mentoring activities. In collecting data writer use questionnaire and observation method. The findings of the research show that the activeness of KAMMI cadres mentoring activities in 2017 is good, that is getting 55-59 score as much as 16 people reaching 51,6%, for category enough to get score between 50-54 counted 12 people reach 38,8% percentage, and for the category of less score of 45-49 as many as 3 people reached the percentage of 9.6%. While the success of performing duties Kader KAMMI Medan good category is 42% that is getting a score between 55-59 with 13 respondents, for enough category is 48.8% with a score between 50-54 with the number of 15 respondents, for the less category is 9.6% ie get a score between 45-49 with the number of 3 respondents.